1991
DOI: 10.1002/jnr.490280312
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of energy metabolism by α‐adrenergic agonists in primary cultures of astrocytes

Abstract: Noradrenaline effects on glucose oxidation were studied in primary cultures of astrocytes. CO2 formation from labeled glucose was enhanced in the presence of noradrenaline. The stimulatory effect by noradrenaline was exerted both on lactate formation (approximately 20%) and on tricarboxylic acid activity (CO2 production from glutamate) (approximately 40%). The effect was, at least partly, exerted on the alpha-ketoglutarate dehydrogenase step. The EC50 value for noradrenaline on lactate formation was significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

1993
1993
2011
2011

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 34 publications
0
26
0
Order By: Relevance
“…The enhancement of pyruvate dehydrogenation (i.e., entry of pyruvate into the TCA cycle), a-K G dehydro genation (i.e., turnover within the TCA cycle) and gluta mine hydrolysis [78][79][80][81][82] in astrocytes might be evoked by a similar mechanism as in heart muscle, and we have reported that the stimulation of pyruvate dehydrogena tion by NA is abolished during incubation in a medium which has been depicted for calcium [78]. However, this is not always the case and the stimulation is not inhibited by ruthenium red (fig.…”
Section: Oxidative Metabolism and Glutamine Hydrolysismentioning
confidence: 99%
“…The enhancement of pyruvate dehydrogenation (i.e., entry of pyruvate into the TCA cycle), a-K G dehydro genation (i.e., turnover within the TCA cycle) and gluta mine hydrolysis [78][79][80][81][82] in astrocytes might be evoked by a similar mechanism as in heart muscle, and we have reported that the stimulation of pyruvate dehydrogena tion by NA is abolished during incubation in a medium which has been depicted for calcium [78]. However, this is not always the case and the stimulation is not inhibited by ruthenium red (fig.…”
Section: Oxidative Metabolism and Glutamine Hydrolysismentioning
confidence: 99%
“…23 Its penetration over the intact bloodbrain barrier is poor 24 but increases in animal models after barrier disruption by intracarotid injection of hypertonic urea; simultaneously, CBF and metabolism increase. 4,5 In bacterial meningitis, a certain extent of barrier disruption is likely to occur.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there are Ca 2+ -mediated increases of glutaminase activity [253] and a direct enhancement of oxidative phosphorylation [252,254]. A similar response occurs in astrocytes, where noradrenaline and α 2 -adrenergic agonists stimulate pyruvate dehydrogenation [40,118,178], α-ketoglutarate dehydrogenation [221] and hydrolysis of glutamine to glutamate [255] ( Table 2). No corresponding effect on α-ketoglutarate dehydrogenation was observed in cultured neurons [256].…”
Section: Oxidative Metabolismmentioning
confidence: 99%
“…However the effect on glucose uptake is exerted on β 3 -adrenoceptors [159] and that on glycolysis on α 1 -adrenoceptors [221][222].…”
Section: Glucose Uptake and Glycolysismentioning
confidence: 99%
See 1 more Smart Citation